Acedia & me : a marriage, monks, and a writer's life - Norris, Kathleen, 1947- (Riverhead Books, 2008)
Kathleen Norris's masterpiece: a personal and moving memoir that resurrects the ancient term acedia, or soul-weariness, and brilliantly explores its relevancy to the modern individual and culture.